INTER-BANK CALL MONEY MARKET TRANSACTION IN INDONESIA - Aries Haryadi; Sahabudin Sidiq (Universitas Islam Indonesia, 2013)
AbstractThis study analyzes the effect of Indonesian Bank loan, the amount of demand deposits, and the Indonesia economic crisis in 1997 on the interbank call money market transactions in Indonesia using a multiple linear regression method. This study finds that the variables influencing the interbank call money market transactions are the interest rate of interbank call money market and the check money. Both variables have positive effect on the interbank money market transactions in Indonesia.Keywords: Loans, Interest Rate, Check Money, Monetary Crisis, Interbank Money Market TransactionsJEL Classification Numbers: G21, G28AbstrakPenelitian ini menganalisis pengaruh pinjaman Bank Indonesia terhadap tingkat bunga pasar uang antar bank, jumlah uang giral, dan krisis ekonomi Indonesia tahun 1997 terhadap transaksi pasar uang antar bank di Indonesia menggunakan metode regresi linier berganda. Penelitian ini menemukan bahwa variabel yang berpengaruh terhadap transaksi pasar uang antar bank tersebut adalah tingkat bunga pasar uang antar bank dan jumlah uang giral. Dua variabel tersebut berpengaruh positif terhadap transaksi pasar uang antar bank di Indonesia.Keywords: Pinjaman, Tingkat Bunga, Uang Giral, Krisis Moneter, Transaksi Pasar Uang antar BankJEL Classification Numbers: G21, G28